2004
DOI: 10.1002/bdra.20021
|View full text |Cite
|
Sign up to set email alerts
|

Maternal autoimmune diseases and immunologically induced embryonic and fetoplacental damage

Abstract: BACKGROUND:Autoimmune diseases are a group of illnesses in which autoantibodies are produced against various organs, presenting with a variety of clinical symptoms. In this review, we discuss the different aspects of autoimmune diseases in pregnancy. We also describe experimental models that help to understand the etiology and pathogenesis of the effects of this maternal disease on the developing embryo, fetus and placenta. METHODS:The possible direct effects of sera or IgG obtained from women with systemic lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…However, pregnancy in patients with SLE and other autoimmune disorders is still a condition carrying some risks for both the mother and baby. These include miscarriage, prematurity, fetal growth disorders, and fetal death, which are thought to be the consequence of immunological changes in the placenta [19][20][21][22][23][24]. In our study, we did not have any cases of SLE-related miscarriages or fetal deaths but the median gestational age at delivery and birthweight in pregnancies of women with SLE were lower than in those without SLE.…”
Section: Discussionmentioning
confidence: 55%
“…However, pregnancy in patients with SLE and other autoimmune disorders is still a condition carrying some risks for both the mother and baby. These include miscarriage, prematurity, fetal growth disorders, and fetal death, which are thought to be the consequence of immunological changes in the placenta [19][20][21][22][23][24]. In our study, we did not have any cases of SLE-related miscarriages or fetal deaths but the median gestational age at delivery and birthweight in pregnancies of women with SLE were lower than in those without SLE.…”
Section: Discussionmentioning
confidence: 55%
“…A few studies have investigated in vitro the effects of sera from women with SLE on embryo and placental tissue cultures. In this context, culture of rat embryos in the presence of human sera from women with SLE and recurrent pregnancy loss resulted in increased embryonic death and abnormality [118]. This same study investigated the effects on human placental tissue (trimester unspecified) and demonstrated reduced proliferation and increased apoptosis -an observation later confirmed on first trimester trophoblast [119].…”
Section: Pregnancy Complications and Slementioning
confidence: 91%
“…The risk factors associated with RPL include parental and fetal chromosome abnormalities, abnormal uterine pathology, endocrine dysfunction, immunologic disease, and thrombophilic disorders ( Table 2). [2][3][4][5][6][7][8][9][10][11][12][13][14][15] 3. The patient's difficulties with RPL and secondary infertility are most likely multifactorial.…”
Section: Possible Answersmentioning
confidence: 99%